MODERN ALGORITHMS AND SOFTWARE FOR INTERPRETATION OF RESISTIVITY LOGGING DATA - M. I. Epov; V. N. Glinskikh; M. N. Nikitenko; A. A. Lapkovskaya; A. R. Leonenko; A. M. Petrov; K. V. Sukhorukova; D. I. Gornostalev (Геодинамика и тектонофизика, 2021)
The electrodynamics of geological media investigates the interrelations of resistivity logging signals and properties of fluid-containing rocks and creates innovative well logging technologies. Its development is inextricably linked with modern techniques for mathematical modeling and quantitative interpretation of high-precision data. In order to increase the information content of galvanic and electromagnetic logging, we have developed algorithms and software for numerical simulation and inversion of field data. In our study of the Cretaceous and Jurassic deposits of West Siberia, a quantitative interpretation of high-frequency electromagnetic and lateral logging signals was carried out. To create geoelectric models, we interpreted the field resistivity logging data by an unconventional quantitative technique based on their joint numerical inversion and estimations of the vertical resistivity of permeable deposits. Another line of our research was aimed at a scientific substantiation of a new technology for mapping and spatial tracking of lateral heterogeneities and oil-promising zones in the Bazhenov Formation. The aim was achieved by using the TEM sounding data on a spatially distributed system of directional and horizontal wells.